Trophic and temporal dynamics of macrophage biology in human inner ear organogenesis - Deng, Yidi; Ehiogu, Boaz; Luca, Emilia; Dabdoub, Alain; Lê Cao, Kim-Anh; Wells, Christine A.; Nayagam, Bryony A. (Frontiers in Immunology, 2025)
Recent single-cell transcriptomic approaches are uncovering the breadth and depth of cell diversity within the mammalian inner ear. Macrophages, detected from fetal week 5 in the human inner ear, persist into adulthood and yet remain poorly understood in terms of their origin and function. Using self-generated and public scRNA-seq data, we identified seven distinct macrophage subtypes spanning fetal weeks 7.5 to 16.4 and adulthood. Each macrophage subtype is linked to specific developmental stages and displays a unique gene expression profile. These findings corroborate earlier histological evidence of resident and non-resident macrophages in both the developing and adult human cochlea. We also showed that the human inner ear is seeded by macrophages from both embryonic and more definitive sources, corroborating studies in mice. By analyzing ligand–receptor interactions, we highlight potential macrophage contributions to inner ear organogenesis. This research provides new insights into the diverse roles of human inner ear macrophages.